Cidades em games: poéticas urbanísticas no espaço de jogo - COSTA JUNIOR, José Maria Teixeira da (Universidade Federal do Pará, 2017)
The work of this dissertation has as its object of study the urban spaces of vídeo games, called here by the word cities in games, from the analysis of its manifestation as models to be used by the discipline of urbanism as a field of visual studies and analyzes urban data. Such as urban planning, in its forms of technical research and design of urban forms, is used for game development, we believe there is an exchange of content very important for the future of these two areas of knowledge. So we start from the conceptual and theoretical analysis based on endoestética proposed by Claudia Giannetti and a theoretical shift using the elements of the city's image of Kevin Lynch in relation to the video game Grand Theft Auto, where we can prove the existence of all these relations.